Preparation of halloysite nanotubes loaded antioxidant and its antioxidative behaviour in natural rubber. (July 2017) - Zhong, Bangchao; Lin, Jing; Liu, Maolin; Jia, Zhixin; Luo, Yuanfang; Jia, Demin; Liu, Fang
Abstract: Halloysite nanotubes (HNTs) loaded poly(1, 2-dihydro-2, 2, 4-trimethyl-quinoline) (RD), HNTs-RD, was successfully prepared and added as filler and antioxidant to form natural rubber (NR) composites. The thermo-oxidative aging behaviour of NR composites and the migration of the loaded RD were investigated by mechanical testing, X-ray photoelectron spectroscopy, differential scanning calorimetry and energy dispersive spectroscopy. For the composites with only HNTs-RD as antioxidant, due to the changed conformation and mobility of the immobilized rubber chains approaching HNTs-RD surface, it took a long time for the released RD from the HNTs lumen to migrate into the free rubber phase, during which the free rubber chains were highly oxidized, leading to the poor thermo-oxidative stability of the rubber composites. For the NR composites with HNTs-RD and free RD, it was found that the free rubber chains were protected against oxygen and heat by the free RD. Besides, the released RD steadily migrated and dispersed into the free rubber phase, ensuring the relatively stable and high concentration of total antioxidant in the free rubber phase for a long time, leading to the much better thermo-oxidative stability compared to the rubber composites with only HNTs-RD. In general, this work is believed to provide better guidance for the preparation of rubber composites with long-term aging resistance.